Comparison of Microbial Pattern Causing Urinary Tract Infection in Female Out- and Hospitalized Patients in Jakarta - YEVA ROSANA; DWIANA OCVIYANTI; ANIS KARUNIAWATI; SYADZA RHIZKY PUTRI AKHMAD (Microbiology Indonesia, 2016)
Urinary Tract Infection (UTI) is an infection in any part of the urinary system. Women are 3 times more likely to have UTI than men. The UTI accounts for 15% infection cases in outpatients and 24% cases in hospitalized patients. Although the most common cause of UTI is certain bacteria, but it was not easy to choose the appropriate antimicrobial therapy. Strategy for choosing empiric antimicrobial treatments for UTI in female out- and hospitalized patients should be based on the pattern of the causative organisms. The aim of this study was to understand the microbial pattern causing UTI in female out- and hospitalized patients in Jakarta. The UTI -1 causative microorganisms were obtained from urine culture containing 100,000 cfu/mL . Twenty nine microorganisms were found as the causative agents of UTI in 317 pregnant women who came to six Community Health Centres (Puskesmas) in Jakarta: Makassar; Pulogadung, Cakung, Pasar Rebo, Duren Sawit, and Kramat Jati for antenatal care. Twenty nine microorganisms were isolated from 114 urine samples of female hospitalized patients who were diagnosed of UTI. The samples were obtained from the Microbiology Laboratory Clinic of FKUI-RSCM. The most common microorganisms causing UTI in female out- and hospitalized patients were Gram negative bacteria. In female outpatients, Klebsiella sp was the most common causative bacteria (31%), followed by Escherichia coli (24.1%). In female hospitalized patients, Escherichia coli was the most common causative bacteria (30%), followed by Candida sp (24.1%) and Klebsiella pneumonia (6.8%). There was more variation in the pattern of UTI causative organisms in hospitalized female patients in comparison to that of the outpatients. Candida sp. was only found in hospitalized UTI patients but not in outpatients.